Impact of Time, Oxygen and Different Anthocyanin to Tannin Ratios on the Precipitate and Extract Composition Using Liquid Chromatography-High Resolution Mass Spectrometry - Garrido-Bañuelos, G.; Buica, A.; de Villiers, A.; du Toit, W.J. (South African Journal of Enology and Viticulture, 2018)
Wine colour and phenolic stability over time are influenced by the amount and nature of phenolics in young wines. The ratio between different phenolic compounds can also be determinant in the colour and phenolic development of red wines. Three different anthocyanin to tannin ratios extracted in a wine-like system were saturated with oxygen several times during sample storage. A LC-HRMS method was used to evaluate the impact of a forced oxidation and of the different extracts on the wine-like composition and on the precipitate formed over time. The extract composition was found to be the most determinant factor for the precipitate formed. Time was also found to be a relevant factor according to the precipitate composition.